Non-dioxin-like organic toxicant PCB153 modulates sphingolipid metabolism in liver progenitor cells: its role in Cx43-formed gap junction impairment - Pierucci, F; Frati, A; Squecco, R; Lenci, E; Vicenti, C; Slavik, J; Francini, F; Machala, M; Meacci, E (Archives of toxicology, 2017)
The non-dioxin-like environmental toxicant 2,2',4,4',5,5'-hexachlorobiphenyl (PCB153), member of a group of persistent organic pollutants wide-spread throughout the environment, reduces gap junction intercellular communication (GJIC), an event possibly associated with tumor promotion. Since very few studies have investigated the signaling effectors and mode(s) of action of PCB153, and it is known that the gap junction (GJ) protein Cx43 can be regulated by the bioactive sphingolipid (SL) sphingosine 1-phosphate (S1P), this in vitro study mainly addresses whether SL metabolism is affected by PCB153 in rat liver epithelial WB-F344 cells. PCB153 treatment obtained significant changes in the S1P/ceramide (Cer) ratio, known to be crucial in determining cell fate. In particular, an increase in S1P at 30 min and a decrease of the bioactive lipid at 3 h were observed, whereas Cer level increased at 1 h and 24 h. Notably, a time-dependent modulation of sphingosine kinase (SphK), the enzyme responsible for S1P synthesis, and of its regulators, ERK1/2 and protein phosphatase PP2A, supports the involvement of these signaling effectors in PCB153 toxicity. Electrophysiological analyses, furthermore, indicated that the lipophilic environmental toxicant significantly reduced GJ biophysical properties, affecting both voltage-dependent (such as those formed by Cx43 and/or Cx32) and voltage-independent channels, thereby demonstrating that PCB153 may act differently on GJs formed by distinct Cx isoforms. SphK down-regulation alone induced GJIC impairment, and, when combined with PCB153, the acute effect on GJ suppression was additive. Moreover, after enzyme-specific gene silencing, the SphK1 isoform appears to be responsible for down-regulating Cx43 expression, while being the target of PCB153 at short-term exposure. In conclusion, we provide the first evidence of novel effectors in PCB153 toxic action in rat liver stem-like cells, leading us to consider SLs as potential markers for preventing GJIC deregulation and, thus, the tumorigenic action elicited by this environmental toxicant.
Keywords: mitogenem aktivovaná proteinkinasa 3; Liver; Protein Phosphatase 2; kultivované buňky; signální transdukce; Electrophysiology; Rats; játra; Sphingosine-1-phosphate; fosfotransferasy s alkoholovou skupinou jako akceptorem; dioxiny; polychlorované bifenyly; Mitogen-Activated Protein Kinase 3; konexin 43; Gap junctions; sfingolipidy; Connexin 43; Signal Transduction; elektrofyziologie; krysa rodu Rattus; Sphingosine; Lysophospholipids; Cells, Cultured; Environmental toxicant non-dioxin-like PCB153; sfingosin; Polychlorinated Biphenyls; zvířata; proteinfosfatasa 2; mezerový spoj; Sphingolipids; Gap Junctions; PP2A; Dioxins; Phosphotransferases (Alcohol Group Acceptor); lysofosfolipidy; Animals